Supply Management Assistance IN "FAEYZA Seamtress" Sewing Business - Fetri Setyo Liyundira (IMPOWERMENT SOCIETY, 2020)
The transaction process of a trading company includes a calculation of the cost of good sold because it contains an inventory of merchandise, so the company needs to specifically record every transaction related to this inventory, and in its development it is still experiencing various problems. The approach method offered to solve partner problems consists of: surveys, interviews, knowledge of inventory methods, recording of inventory methods, assistance and equipment, monitoring and evaluation. This Community Service activity is expected to provide a computerized recording system for inventory methods and the procurement of adequate equipment to support the sewing process.